Incident light and morphology determine coral productivity along a shallow to mesophotic depth gradient. Issue 19 (30th August 2021) - Lesser, Michael P.; Slattery, Marc; Mobley, Curtis D.
Abstract: While the effects of irradiance on coral productivity are well known, corals along a shallow to mesophotic depth gradient (10–100 m) experience incident irradiances determined by the optical properties of the water column, coral morphology, and reef topography. Modeling of productivity (i.e., carbon fixation) using empirical data shows that hemispherical colonies photosynthetically fix significantly greater amounts of carbon across all depths, and throughout the day, compared with plating and branching morphologies. In addition, topography (i.e., substrate angle) further influences the rate of productivity of corals but does not change the hierarchy of coral morphologies relative to productivity. The differences in primary productivity for different coral morphologies are not, however, entirely consistent with the known ecological distributions of these coral morphotypes in the mesophotic zone as plating corals often become the dominant morphotype with increasing depth. Other colony‐specific features such as skeletal scattering of light, Symbiodiniaceae species, package effect, or tissue thickness contribute to the variability in the ecological distributions of morphotypes over the depth gradient and are captured in the metric known as the minimum quantum requirements. Coral morphology is a strong proximate cause for the observed differences in productivity, with secondary effects of reef topography on incident irradiances, and subsequently the community structure of mesophotic corals. Abstract : Corals along a shallow to mesophotic depth gradient (10–100 m) experience incident irradiances determined by their morphology and reef topography. Both the substrate angle (i.e., topography) and a hierarchy of colony morphologies have significant, and repeatable, effects on modeled productivity in mesophotic corals.